Pengaruh Kata “Seng” dalam Berkomunikasi Bahasa Indonesia di Pergaulan Generasi Z - Salsabila Azzahra; Rabiah Fitrah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Language continues to develop following social dynamics, especially among Generation Z who are known to be creative and practical, as seen in the use of the word “Seng” as a form of affection in everyday communication. This phenomenon raises questions about its influence on the structure of the Indonesian language. The purpose of this study was to determine the impact of the word “Seng” in communicating Indonesian in Generation Z's social circles. The method used was a phenomenological study. The results of the study found that the use of the word “Seng” reflects the creativity and social identity of Generation Z in informal communication, but raises concerns about the degradation of good and correct Indonesian, especially in formal and educational contexts. It is hoped that this study can add to the literature on communication and Indonesian studies. Then, it is hoped that the results of the study can be a reference for further researchers who are interested in researching similar topics.